Photoacclimation Responses of the Brown Macroalga Sargassum Cymosum to the Combined Influence of UV Radiation and Salinity: Cytochemical and Ultrastructural Organization and Photosynthetic Performance. (10th January 2014) - Polo, Luz K.; de, Marthiellen R.; Kreusch, Marianne; Pereira, Debora T.; Costa, Giulia B.; Simioni, Carmen; Ouriques, Luciane C.; Chow, Fungyi; Ramlov, Fernanda; Maraschin, Marcelo; Bouzon, Zenilda L.; Schmidt, Éder C.
Abstract The photoacclimation responses of the brown macroalga Sargassum cymosum were studied to determine its cytochemical and ultrastructural organization, as well as photosynthetic pigments and performance. S. cymosum was cultivated in three salinities (30, 35 and 40 psu) under four irradiation treatments: PAR‐only, PAR + UVA, PAR + UVB and PAR + UVA + UVB. Plants were exposed to PAR at 70 μmol photons m−2 s−1, PAR + UVB at 0.35 W m−2 and PAR +UVA at 0.70 W m−2 for 3 h per day during 7 days in vitro. Growth rate was not significantly affected by any type of radiation or salinity. The amount of pigments in S. cymosum was significantly influenced by the interaction of salinity and radiation treatments. Compared with PAR‐only, UVR treatments modified the kinetics patterns of the photosynthesis/irradiance curve. After exposure to UVR, S. cymosum increased cell wall thickness and the presence of phenolic compounds. The number of mitochondria increased, whereas the number of chloroplasts showed few changes. Although S. cymosum showed insensitivity to changes in salinity, it can be concluded that samples treated under four irradiation regimes showed structural changes, which were more evident, but not severe, under PAR + UVB treatment.